2015
DOI: 10.1080/01434632.2015.1083573
|View full text |Cite
|
Sign up to set email alerts
|

The competence and warmth of Thai students’ attitudes towards varieties of English: the effect of gender and perceptions of L1 diversity

Abstract: Previous language attitude research indicates that presenting speech forms allows listeners to index information about and attach social meaning to the perceived group(s) of speakers. Despite the volume of research undertaken elsewhere in Asia, there appear to be no indepth studies investigating Thai nationals' evaluations of specific varieties of English speech. This large-scale study examines 204 Thai university students' attitudes towards forms of UK, US, Japanese, Chinese, Thai and Indian English, provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(11 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…As for the second and third questions in the survey, most participants reported that they usually listen to and prefer American and British Englishes over any other variety. These findings coincide with most attitude studies that included an IC English variety (Almegren, 2018 ; Buckingham, 2014 , 2015 ; Li & He, 2009 ; McKenzie, 2008 ; McKenzie & Gilmore, 2015 ; McKenzie et al, 2016 ; Meer et al, 2021 ; Yook & Lindemann, 2013 , Zoghbor, 2014 ). The fourth question in the survey was intended to give participants the opportunity to evaluate the female speaker more openly compared to the closed-ended nature of the SDS.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…As for the second and third questions in the survey, most participants reported that they usually listen to and prefer American and British Englishes over any other variety. These findings coincide with most attitude studies that included an IC English variety (Almegren, 2018 ; Buckingham, 2014 , 2015 ; Li & He, 2009 ; McKenzie, 2008 ; McKenzie & Gilmore, 2015 ; McKenzie et al, 2016 ; Meer et al, 2021 ; Yook & Lindemann, 2013 , Zoghbor, 2014 ). The fourth question in the survey was intended to give participants the opportunity to evaluate the female speaker more openly compared to the closed-ended nature of the SDS.…”
Section: Discussionsupporting
confidence: 80%
“…In contexts where English is neither institutionalized nor a legacy of colonialism, language attitude research has often used Verbal Guise Tests (VGTs) to explore attitudes about local Englishes, and these are typically carried out in comparison to measuring attitudes toward inner circle varieties (e.g., McKenzie, 2008 ; Sasayama, 2013 ). There are an increasing number of studies that invite research participants to respond to regionally relevant varieties from the EC as well (e.g., Buckingham, 2015 ; McKenzie & Gilmore, 2015 ; McKenzie et al, 2016 ; Meer et al, 2021 ; Yook & Lindemann, 2013 ); however, these studies have demonstrated that participants favor IC varieties as models for learning. When IC varieties are included as part of the study, solidarity measures show that participants tend to view their own local Englishes more positively, while power measures reveal that IC Englishes used by educated speakers from the USA and the UK remain idealized varieties for institutional and international purposes.…”
Section: Introductionmentioning
confidence: 99%
“…A high degree of consistency has been found from the data collected in these studies. More specifically, it has been widely demonstrated that speakers of standard language varieties are usually rated more positively in terms of status when compared to speakers of forms deemed non-standard (see Dragojevic and Giles 2014;Edwards 2011;McKenzie, Kitikanan, and Boriboon 2016). In the case of England, for instance, researchers have demonstrated that English nationals, historically, tend to evaluate standard varieties associated with English speakers from the south of England, such as Received Pronunciation (RP) and Standard Southern British English (SSBE), more favourably in comparison with those speakers of linguistic forms of English perceived to be non-standard and, most particularly, with regards to the English of speakers from urban areas in the north of England, e.g., in Liverpool and Newcastle (Garrett 2010;Giles 1970).…”
Section: Language Attitudesmentioning
confidence: 99%
“…The experimental design used in the current study had a few limitations. Firstly, studies on language attitudes tend to establish accent categorization with larger samples of ratings or through a larger focus group of expert raters to avoid impressionistic judgments [ 48 ]. However, due to limited time and funding, we only managed to recruit two expert judges for categorization.…”
Section: Discussionmentioning
confidence: 99%